2021
DOI: 10.1371/journal.pone.0250516
|View full text |Cite
|
Sign up to set email alerts
|

A high throughput reporter virus particle microneutralization assay for quantitation of Zika virus neutralizing antibodies in multiple species

Abstract: Zika virus is a Flavivirus, transmitted via Aedes mosquitos, that causes a range of symptoms including Zika congenital syndrome. Zika has posed a challenging situation for health, public and economic sectors of affected countries. To quantitate Zika virus neutralizing antibody titers in serum samples, we developed a high throughput plate based Zika virus reporter virus particle (RVP) assay that uses an infective, non-replicating particle encoding Zika virus surface proteins and capsid (CprME) and a reporter ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…To assess the ability of functional oleosin-based micelles to block viral entry, we used SARS-CoV-2 pseudovirus particles (PVs) as a model to test the inactivation effectiveness of different micellar compositions. PVs are essentially liposomes with the SARS-CoV-2 Spike S1 protein at the membrane, making them antigenically alike to the wild-type virus . PVs have a second-generation lentiviral core containing a green fluorescence protein (GFP) gene, which is expressed upon transduction .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the ability of functional oleosin-based micelles to block viral entry, we used SARS-CoV-2 pseudovirus particles (PVs) as a model to test the inactivation effectiveness of different micellar compositions. PVs are essentially liposomes with the SARS-CoV-2 Spike S1 protein at the membrane, making them antigenically alike to the wild-type virus . PVs have a second-generation lentiviral core containing a green fluorescence protein (GFP) gene, which is expressed upon transduction .…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of higher-diameter peaks in both Figure 2B, corresponding to Oleo-LCBx, and Figure S2, corresponding to all the blends, could also mean that some Spike S1 protein at the membrane, making them antigenically alike to the wild-type virus. 36 PVs have a second-generation lentiviral core containing a green fluorescence protein (GFP) gene, which is expressed upon transduction. 37 PVs have been proven to serve as a viable, non-replicating model for testing transductions by dengue, zika, and SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of effective vaccines, TBEV continues to pose a considerable threat to public health due to its expanding geographical distribution and the increasing number of reported cases (1) RVP-based SNTs for different orthoflaviviruses have been established using different cell lines, including BHK-J cells (24), BHK-21 cells (26), Vero cells (25), and HUH-7.5 cells (27). In our experiments, we found that HUH7 cells were well suited for the effective execution of TBEV, YFV, DENV, ZIKV, WNV, and JEV RVP SNTs.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing activity in sera from the U.S. donors was measured at days 0,10,14,16,28,90,180,270 and 360 post vaccination (Figure 1A-B) with a widely employed West Nile virus-based reporter viral particle system (RVP) (Pierson et al, 2006). RVPs faithfully recapitulate the behavior of authentic flaviviruses in studies of virus structure, function, and antibody recognition and neutralization (Bohning et al, 2021;Bradt et al, 2019;Dowd et al, 2011;Goo et al, 2016Goo et al, , 2017Mattia et al, 2011) (Figure S1). Serum neutralizing titers against RVPs bearing the structural proteins C-prM-E from the YF-17D vaccine strain (RVP17D) and the virulent African strains Asibi (RVPAsibi) and China (ex-Angola) (RVPChina) (Figure 1A) rose sharply, peaked at days 14-16, and remained stable thereafter, as reported previously (Lindsey et al, 2018;Wec et al, 2020;Wieten et al, 2016).…”
Section: The Brazilian Isolate Yfv-es-504 Is Poorly Neutralized By Yf...mentioning
confidence: 95%